2018
DOI: 10.4314/tjpr.v17i8.25
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of methanol extracts of selected plants on proliferation of two human melanoma cell lines

Abstract: The aim of the current study was to investigate the invitro antiproliferative activity of methanolic extracts of six plants regardless of their claimed ethnopharmacological application. Methods: Methanol extracts of different parts of Glycyrrhizaglabra L. (Licorice),Matricariachamomilla L. (Chamomile), Salvia triloba L. (Sage), Rheum palmatum L. (Rhubarb), Trigonellafoenum-graecumL. (Fenugreek) and Sambucusebulus L. (Dwarf Elder) were prepared. The antiproliferative effects of the extracts were tested on two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…These studies revealed anti-diabetic, anti-oxidant, anti-inflammatory as well as anti-tumor activities of plant extracts and isolates. These effects were mainly attributed to plant phenolics, flavonoids, coumarins, terpenes and carotenoids, such as rosmarinic acid (phenolic) and carnosic acid (CA, terpene) [3,4,5,6,7]. In this study, we focused on two Salvia species, Salvia fruticosa Mill.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies revealed anti-diabetic, anti-oxidant, anti-inflammatory as well as anti-tumor activities of plant extracts and isolates. These effects were mainly attributed to plant phenolics, flavonoids, coumarins, terpenes and carotenoids, such as rosmarinic acid (phenolic) and carnosic acid (CA, terpene) [3,4,5,6,7]. In this study, we focused on two Salvia species, Salvia fruticosa Mill.…”
Section: Introductionmentioning
confidence: 99%
“…(SF) and Salvia pomifera L. (SP), which are used in Crete as traditional medicines, however clinical evidence for these traditional indications in accordance with EBM (Evidence Based Medicine) is lacking. In particular, SF plants, which are the most important sage in the United States, have shown a cytotoxic effect in several cancer cell lines in vitro, including human colon, pancreatic, breast, and cervical carcinoma and also leukemic and melanoma cell lines [2,3,4,6,7,8,9]. As with other Salvia species, SF chemoprotective properties are cell line dependent and several mechanisms for the molecular pathways’ activation have been proposed, such as DNA damage prevention, enhanced DNA repair, cell proliferation inhibition and apoptosis induction [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Salvia fruticosa metanol ekstraktlarının, melanom hücre hattı WM 136.1A proliferasyonu üzerinde doza bağlı olarak anlamlı bir sitotoksik etki gösterdiği bildirilmiştir [80].…”
Section: Antikanser Etkileriunclassified
“…Melanoma is considered as the most aggressive type of skin cancer, and patients with local or distant metastasis of melanoma have a poor prognosis [1]. The treatment for melanoma remains a challenge due to pre-existing or acquired drug resistance [2].…”
Section: Introductionmentioning
confidence: 99%